Criminal liability of corporate bodies for polluting the environment: Sharia and law perspectives - Ashour, Ameel Jabbar; Abdul Wahab, Harlida (IRAJ, 2016)
the purpose of this paper is to determine the criminal liability of a corporate body that is not specified as a crime for polluting the environment within man-made laws except if it is committed by a natural person (human being).The offender of environmental crime can either be a natural person or a corporate body. However, the determination of the responsibility of corporate bodies for this particular crime has been the subject of much debate between supporters and opponents within the legal community.It should be noted that the damage caused by a natural person in the field of environmental crimes is limited as compared with that of a corporate body, especially by the industrial companies in major industrialized countries.Therefore, this paper seeks to find out the real position of a corporate body’s criminal liability for the crimes committed against the environment in the Islamic and legal jurisprudence. This paper adopts qualitative method of research. Since determining the criminal liability of corporate bodies concerning crimes of polluting the environment in the light of Islamic Sharia is worth all the attention due to the continuous increase in the number of the corporate bodies as well as its great influence in the social and economic life of society.Jurisprudence has been split between supporters and opponents of this new direction of the liability of these persons concerning their crimes against the environment.The rage of disputes at the level of jurisprudence from time to time, has led to a need to adopt a more practical approach in the implementation of criminal legislation that is a deterrent against corporate bodies on the issues in order to protect the environment.